Método de aspersión en seco como alternativa para la producción de dulce de agave (agave americana l) en polvo. - Chicaiza Vilca, Alex Orlando (2019)
The research was conducted at the Technical University of Cotopaxi, Agroindustrial Engineering Career, and focused on obtaining a powder agave candy by the dry spray method as an alternative for its production in Ecuador. To obtain this sweet powder was collected the agave sweet as raw material and the dry spray equipment, and a factorial design of completely random blocks AxB was used, which resulted in 9 treatments with one repetition. In factor A, the concentration of dissolved solids in an American agave sweet established with three levels (20, 25 and 30 ° Brix) and in factor B, the drying parameters to be taken into account for the method of dry sprinkling with three levels (90 ° C: 500 ml / h, 130 ° C: 700 ml / h, 170 ° C: 900 ml / h) (inlet temperature: feed flow). For the dry sprinkling process, it was necessary to add an encapsulating vehicle which in this case is maltodextrin by 20% in relation to the total weight of the agave candy in a volume of 500 ml. Through the physical-chemical analysis carried out in the 9 treatments, moisture, sweetening power and yield were determined, and the best treatment was chosen where there is evidence that there is a significant difference. In the microbiological analyzes, the presence of mesophilic aerobes with a result of 1.6 * 105 CFU / gr, total coliforms <10 CFU / gr, molds 1.6 * 103 <10 CFU / gr and yeasts <10 CFU / gr, taking into account of RM Standard No. 615-2003 SA / DM, INEN 0259 (white sugar) and a MAPRYSER technical sheet.